UTILIZATION OF TIKTOK AND YOUTUBE AS LEARNING MEDIA TO ADDRESS POST-PANDEMIC ACADEMIC BACKWARDNESS IN RURAL AREAS - A, Elisabeth; Kurniawan, Trio (JOEEL (Journal of English Education and Literature), 2024)
The COVID-19 pandemic has posed many challenges to education delivery, especially in rural areas. This study aims to analyze the perceptions and experiences of students in rural areas using TikTok and YouTube as learning media during and after the pandemic. This research uses mixed methods (quantitative and qualitative). The results show that students in rural areas face internet access constraints and low learning motivation. However, they are interested in using TikTok and YouTube, which are considered interactive and easily accessible materials. This study concludes that both digital platforms can potentially overcome the academic backwardness of students in post-pandemic rural areas. Specifically, quantitative data collected through closed questionnaires revealed that most students in rural areas rely on unstable mobile internet and devices, resulting in poor connectivity. The qualitative, open-ended questionnaire highlighted decreased motivation and increased stress among about half of the respondents. Despite the decrease in motivation, the students remained enthusiastic about using TikTok and YouTube for self-directed learning. They found the platforms engaging, flexible, and enabled discussion with peers. This study suggests that increasing the interactive capacity of these digital tools could promote effective online education for underserved groups, reducing the pandemic gap.